Cultural autonomy in contemporary Europe - Smith, David J.; Cordell, Karl 1956- (Routledge, 2008)
In this volume, some of the world's leading scholars involved in researching the fields of ethnopolitics, nationalism and ideas of nation and state, have come together to produce a work that is both original and accessible. The volume explores the rich, but sadly neglected tradition of thought on non-territorial cultural autonomy as exemplified by the work of Karl Renner and Otto Bauer and the European Nationalities Congress of the 1920s. Through a combination of theoretical analysis and case study approaches, the authors challenge conventional thinking on how best to reconcile competing claims over territory and cultural expression. Drawing upon a range of examples from countries such as Russia, Romania and Hungary, and by comparing the situation of territorially-based ethnic minorities with those - principally the Roma - who lack identification with a given state or states, the authors of this volume seek to supply answers and question received truths.